An overview of the historical context for Jamun's diverse medicinal properties (Sciences of Phytochemistry, 2023)
Syzygium cumini, also known as Jamun, Jambul, or Indian blackberry, is a species of tree native to the Indian subcontinent. A comprehensive literature review shows that Jamun can be considered one of the most versatile herbal medicines with anti-diabetic, anti-oxidant, anti-inflammatory, and other properties. This review aims to investigate and understand the previous research on Jamun, including its pharmacognosy and pharmacological history, to confirm its potential to treat a variety of illnesses. The study also examined the current pharmaceutical formulations available in the market to understand the potential for developing medications from the components of Jamun. To comprehend the available studies, the analytical backdrop is also reviewed. Despite being the focus of many research studies, there are still many unanswered questions regarding Jamun. Therefore, the best formulations or products may be produced in these sectors, possibly through nutraceuticals, to support improved pharmacological aspects or health promotion. This review will help identify unexplored areas where specific tasks related to Jamun can be done.